Development of Mathematics Teaching Materials Based on Metacognition Approaches to Improve Students' Mathematical Reasoning Ability - Silvia Yanti; Amin Fauzi; Mulyono Mulyono (Mathematics Education Study Program, 2021)
This study aims to describe: (1) the validity, practicality, and effectiveness of the teaching materials developed based on expert validators. practitioners, as well as based on the implementation of teaching materials; 2) To describe the improvement of students' mathematical reasoning abilities by using teaching materials with a metacognition approach; This research is a development research conducted in two stages, namely the first stage of developing learning tools through the metacognition approach using the Dick & Carey development model and the second stage of testing teaching materials based on the metacognition approach developed in classes VIII-1 and VIII-4 MTs Hifzhil Qur. 'an Medan. (1) the developed teaching materials meet the valid and effective criteria based on the expert validator and practitioner assessment; and effective based on classical completeness, student responses, and the ability of teachers to manage learning; (2) in the first trial there was an increase in mathematical reasoning abilities using the teaching materials developed in the low category, namely 0.24 and in the second trial there was an increase in mathematical reasoning abilities using the teaching materials developed in the medium category, which was 0.52.